Chronic spontaneous urticaria: cutaneous reaction and laboratory aspects - Vitor Celso M. Campos; Letícia Yassumoto; Odilon M. Almeida Filho; Roseli N. S. Antunes; Zamir Calamita
ABSTRACT Introduction: The chronic spontaneous urticaria (CSU) is a cutaneous reaction characterized by the formation of episodic and recurrent erythematous papules, usually pruritic, which etiology may be associated with an autoimmune response resulting from the action of immunoglobulin subclass G (IgG) of autoantibodies directed against the immunoglobulin subclass E (IgE) receptors of cutaneous mast cells or against IgE bound to mast cells. The autologous serum skin test (ASST) is a screening test that indicates the presence of these autoantibodies in patients with CSU. Objective: To check for differences in ASST results among patients with CSU and the control group with other hypersensitivities. Material and method: This is a cross-sectional case-control study, in which 49 adults were analyzed, 27 with CSU and 22 with other hypersensitivity reactions. ASST, CD123, estimation of IgG bound to basophil, mean platelet volume (MPV), antinuclear antibody (ANA), thyroid-stimulating hormone (TSH), anti-thyroid peroxidase antibody (TPOab), erythrocyte sedimentation rate (ESR) and the total IgE were performed in both groups. Results: The ASST, shown positive results in 16 (59.2%) the patients with CSU and in five (22.7%) from the control group, with statistical significance. For the other variables above described, there was no statistical difference. Conclusion: A higher ASST positivity was found in CSU patients compared to patients with other hypersensitivities, and further studies with larger sample are needed for better analysis of other variables.